Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas - Moreau, Sebastien; Lannuzel, Delphine; Janssens, J.; Arroyo, Mar; Corkill, M; Cougnon, Eva; Genovese, C.; Legresy, Benoit; Lenton, Andrew; Puigcorbe, V.; Ratnarajah, L.; Rintoul, Steve; et al. (Journal of Geophysical Research: Oceans, 2019)
In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2. Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a)/m2, respectively) and net community production (5.3 and 4.6 mol C/m2, respectively) were approximately 3 times those measured in the Dalton polynya (average of 122 mg Chl a/m2 and 1.8 mol C/m2). Phytoplankton communities also differed between the polynyas. Diatoms were thriving in the Mertz and Ninnis polynyas but not in the Dalton polynya, where Phaeocystis antarctica dominated. These strong regional differences were explored using physiological, biological, and physical parameters. The most likely drivers of the observed higher productivity in the Mertz and Ninnis were the relatively shallow inflow of iron-rich modified Circumpolar Deep Water onto the shelf as well as a very large sea ice meltwater contribution. The productivity contrast between the three polynyas could not be explained by (1) the input of glacial meltwater, (2) the presence of Ice Shelf Water, or (3) stratification of the mixed layer. Our results show that physical drivers regulate the productivity of polynyas, suggesting that the response of biological productivity and carbon export to future change will vary among polynyas.
Keywords: Sørishavet; biomasse; brehylle; fytoplankton; havis; isbrem; isshelf; marin biologi; oseanografi; polynja; sjøis

Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines - Sun, Sainan; Hattermann, Tore; Pattyn, Frank; Nicholls, Keith W; Drews, Reinhard; Berger, Sophie (Geophysical Research Letters, 2019)
The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase-sensitive radio-echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results suggest an intricate mechanism in which topographic waves control the seasonal melt rate variability near the grounding line. This mechanism has not been considered before and has the potential to enhance local melt rates without advecting different water masses. As topographic waves seem to strengthen in a stratified ocean, the freshening of Antarctic surface water, predicted by observations and models, is likely to increase future basal melting in this area.
Keywords: Sørishavet; glasiologi; isshelf; klimatologi; oseanografi; smelting; vannmasser

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Seasonal Outflow of Ice Shelf Water Across the Front of the Filchner Ice Shelf, Weddell Sea, Antarctica - Darelius, Elin Maria K; Sallée, Jean-Baptiste (Geophysical Research Letters, 2018)
Keywords: Sørishavet; Weddellhavet; bunnvann; isfront; isshelf; oseanografi

Ice-rise stratigraphy reveals changes in surface mass balance over the last millennia in Dronning Maud Land - Goel, Vikram; Martín, Carlos; Matsuoka, Kenichi (Journal of Glaciology, 2018)
We use ice flow modelling to simulate the englacial stratigraphy of Blåskimen Island, an ice rise in Dronning Maud Land and elucidate the evolution of this data-sparse region. We apply a thermo-mechanically coupled Elmer/Ice model to a profile along flowlines and through the ice-rise summit, where surface mass balance (SMB), flow velocity and ice stratigraphy were recently measured. We conclude that: (i) the ice rise is presently thickening at a rate of 0.5~0.6 m ice equivalent per year (mieq a−1), which is twice an earlier estimate using the field data and the input–output method; (ii) present thickening started 20–40 years in the past, before which the ice rise was in a steady state; (iii) SMB contrast between the upwind and downwind slopes was stronger than the present value by ~23% (or 0.15 mieq a−1) prior to ~1100 years ago. Since then, this contrast has been decreasing overall. We surmise that these SMB changes are likely a result of synoptic-scale atmospheric changes, rather than local atmospheric changes controlled by local ice topography. Our technique effectively assimilates geophysical data, avoiding the complexity of ice flow beneath the ice divide. Thus, it could be applied to other ice rises to elucidate the recent glacial retreat.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

A New Bathymetry for the Southeastern Filchner-Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History - Rosier, Sebastian H R; Hofstede, Coen; Brisbourne, Alex Mark; Hattermann, Tore; Nicholls, Keith William; Davis, Peter E D; Anker, Paul; Hillenbrand, Claus-Dieter; Smith, Andrew M; Corr, Hugh F (Journal of Geophysical Research: Oceans, 2018)
The Filchner-Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub-ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo-ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub-ice shelf melt rates.
Keywords: Sørishavet; batymetri; brehylle; innlandsis; isbrem; isshelf; klima; oseanografi; tidevann

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi

Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica - Goel, Vikram; Brown, Joel; Matsuoka, Kenichi (The Cryosphere, 2017)
The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below the current sea level. Shallow radar-detected isochrones dated with a firn core reveal that the surface mass balance is higher on the south-eastern (upwind) slope than on the north-western (downwind) slope by ∼ 37 %, and this pattern has persisted for at least the past decade. Moreover, arches in radar stratigraphy suggest that the summit of the ice rise has been stable for ∼ 600 years. Ensemble estimates of the mass balance using the input–output method show that this ice rise has thickened by 0.12–0.37 m ice equivalent per year over the past decade.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Channelized Melting Drives Thinning Under a Rapidly Melting Antarctic Ice Shelf - Gourmelen, Noel; Goldberg, Dan N; Snow, Kate; Henley, Sian F; Bingham, Robert G; Kimura, Satoshi; Hogg, Anna E; Shepherd, Andrew; Mouginot, Jeremie; Lenaerts, Jan T M; Ligtenberg, Stefan R M; van de Berg, Willem Jan (Geophysical Research Letters, 2017)
Ice shelves play a vital role in regulating loss of grounded ice and in supplying freshwater to coastal seas. However, melt variability within ice shelves is poorly constrained and may be instrumental in driving ice shelf imbalance and collapse. High-resolution altimetry measurements from 2010 to 2016 show that Dotson Ice Shelf (DIS), West Antarctica, thins in response to basal melting focused along a single 5 km-wide and 60 km-long channel extending from the ice shelf's grounding zone to its calving front. If focused thinning continues at present rates, the channel will melt through, and the ice shelf collapse, within 40–50 years, almost two centuries before collapse is projected from the average thinning rate. Our findings provide evidence of basal melt-driven sub-ice shelf channel formation and its potential for accelerating the weakening of ice shelves.
Keywords: Sørishavet; glasiologi; havnivå; innlandsis; isbrem; isshelf; smelting

Oceanographic Controls on the Variability of Ice-Shelf Basal Melting and Circulation of Glacial Meltwater in the Amundsen Sea Embayment, Antarctica - Kimura, Satoshi; Jenkins, Adrian; Regan, Heather; Holland, Paul R; Assmann, Karen M; Whitt, Daniel B; Van Wessem, Melchoir; van de Berg, Willem Jan; Reijmer, Carleen H; Dutrieux, Pierre (Journal of Geophysical Research: Oceans, 2017)
Ice shelves in the Amundsen Sea Embayment have thinned, accelerating the seaward flow of ice sheets upstream over recent decades. This imbalance is caused by an increase in the ocean-driven melting of the ice shelves. Observations and models show that the ocean heat content reaching the ice shelves is sensitive to the depth of thermocline, which separates the cool, fresh surface waters from warm, salty waters. Yet the processes controlling the variability of thermocline depth remain poorly constrained. Here we quantify the oceanic conditions and ocean-driven melting of Cosgrove, Pine Island Glacier (PIG), Thwaites, Crosson, and Dotson ice shelves in the Amundsen Sea Embayment from 1991 to 2014 using a general circulation model. Ice-shelf melting is coupled to variability in the wind field and the sea-ice motions over the continental shelf break and associated onshore advection of warm waters in deep troughs. The layer of warm, salty waters at the calving front of PIG and Thwaites is thicker in austral spring (June–October) than in austral summer (December–March), whereas the seasonal cycle at the calving front of Dotson is reversed. Furthermore, the ocean-driven melting in PIG is enhanced by an asymmetric response to changes in ocean heat transport anomalies at the continental shelf break: melting responds more rapidly to increases in ocean heat transport than to decreases. This asymmetry is caused by the inland deepening of bathymetry and the glacial meltwater circulation around the ice shelf.
Keywords: Amundsenhavet; Sørishavet; batymetri; brehylle; glasiologi; isbrem; ismeltvann; isshelf; klimatologi; oseanografi

Antarctic ice rises: small in size but big on impact - Matsuoka, Kenichi (Fram forum, 2017)
Ice discharge from the Antarctic Ice Sheet directly impacts global sea level, making ice sheet dynamics a central topic in antarctic research. Glaciologists are studying a poorly understood but potentially important phenomenon that looks like a little hill of ice. They call these hills “ice rises”.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf

Seasonal cycle of hydrography on the eastern shelf of the Filchner Trough, Weddell Sea, Antarctica - Ryan, Svenja; Hattermann, Tore; Darelius, Elin Maria K; Schröder, Michael (Journal of Geophysical Research: Oceans, 2017)
Keywords: Sørishavet; Weddellhavet; hydrografi; isshelf; kontinentalsokkel; kontinentalsokler

A constitutive framework for predicting weakening and reduced buttressing of ice shelves based on observations of the progressive deterioration of the remnant Larsen B Ice Shelf - Borstad, Chris; Khazendar, Ala; Scheuchl, Bernd; Morlighem, Mathieu; Larour, Eric; Rignot, Eric (Geophysical Research Letters, 2016)
The increasing contribution of the Antarctic Ice Sheet to sea level rise is linked to reductions in ice shelf buttressing, driven in large part by basal melting of ice shelves. These ocean-driven buttressing losses are being compounded as ice shelves weaken and fracture. To date, model projections of ice sheet evolution have not accounted for weakening ice shelves. Here we present the first constitutive framework for ice deformation that explicitly includes mechanical weakening, based on observations of the progressive degradation of the remnant Larsen B Ice Shelf from 2000 to 2015. We implement this framework in an ice sheet model and are able to reproduce most of the observed weakening of the ice shelf. In addition to predicting ice shelf weakening and reduced buttressing, this new framework opens the door for improved understanding and predictions of iceberg calving, meltwater routing and hydrofracture, and ice shelf collapse.
Keywords: Antarktis; glasiologi; global oppvarming; havnivåstigning; innlandsis; isbrem; isshelf; smelting

Observed vulnerability of Filchner-Ronne Ice Shelf to wind-driven inflow of warm deep water - Darelius, Elin Maria K; Fer, Ilker; Nicholls, Keith William (Nature Communications, 2016)
Keywords: Antarktis; Weddellhavet; isshelf; oseanografi; sjøvann

Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C; Firing, Yvonne (Journal of Geophysical Research: Oceans, 2016)
Ice shelves around Antarctica are vulnerable to an increase in ocean-driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice-shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice-shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation-rate-based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin-Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting.
Keywords: Sørishavet; batymetri; brehylle; isbrem; isshelf; klimatologi; målinger; oseanografi; smeltevann; vannmasser

On-ice vibroseis and snowstreamer systems for geoscientific research - Eisen, Olaf; Hofstede, Coen; Diez, Anja; Kristoffersen, Yngve; Lambrecht, Astrid; Mayer, Christoph; Blenkner, Rick; Hilmarsson, Sverrir (Recent Advance in Polar Seismology: Global Impact of the International Polar Year, 2015)
We present implementations of vibroseis system configurations with a snowstreamer for over-ice long-distance seismic traverses (>100 km). The configurations have been evaluated in Antarctica on ice sheet and ice shelf areas in the period 2010–2014. We discuss results of two different vibroseis sources: Failing Y-1100 on skis with a peak force of 120 kN in the frequency range 10–110 Hz; IVI EnviroVibe with a nominal peak force of 66 kN in the nominal frequency range 10–300 Hz. All measurements used a well-established 60 channel 1.5 km snowstreamer for the recording. Employed forces during sweeps were limited to less than 80% of the peak force. Maximum sweep frequencies, with a typical duration of 10 s, were 100 and 250 Hz for the Failing and EnviroVibe, respectively. Three different concepts for source movement were employed: the Failing vibrator was mounted with wheels on skis and pulled by a Pistenbully snow tractor. The EnviroVibe was operated self-propelled on Mattracks on the Antarctic plateau. This lead to difficulties in soft snow. For later implementations the EnviroVibe with tracks was put on a polyethylene (PE) sled. The sled had a hole in the center to lower the vibrator baseplate directly onto the snow surface. With the latter setup, data production varied between 20 km/day for 6-fold and 40 km/day for single fold for 9 h/day of measurements. The combination of tracks with the PE-sled was especially advantageous on hard and rough surfaces because of the flexibility of each component and the relatively lose mounting. The systems presented here are suitable to obtain data of subglacial and sub-seabed sediment layers and englacial layering in comparable quality as obtained from marine geophysics and land-based explosive surveys. The large offset aperture of the streamer overcomes limitations of radar systems for imaging of steep along-track subglacial topography. With joint international scientific and logistic efforts, large-scale mapping of Antarctica's and Greenland's subglacial geology, ice-shelf cavity geometries and sea-bed strata, as well as englacial structures can be achieved.
Keywords: Dronning Maud Land; isshelf; seismologi; teknologi

Polynya dynamics drive primary production in the Larsen A and B embayments following ice shelf collapse - Cape, Mattias R.; Vernet, Maria; Kahru, Mati; Spreen, Gunnar (Journal of Geophysical Research: Oceans, 2014)
The climate-driven collapses of the Larsen A and B ice shelves have opened up new regions of the coastal Antarctic to the influence of sea ice resulting in increases in seasonal primary production. In this study, passive microwave remote sensing of sea ice concentration and satellite imagery of ocean color are employed to quantify the magnitude of and variability in open water area and net primary productivity (NPP) in the Larsen embayments between 1997 and 2011. Numerical model output provides context to analyze atmospheric forcing on the coastal ocean. Following ice shelf disintegration the embayments function as coastal, sensible heat polynyas. The Larsen A and B are as productive as other Antarctic shelf regions, with seasonally averaged daily NPP rates reaching 1232 and 1127 mg C m−2 d−1 and annual rates reaching 200 and 184 g C m−2 yr−1, respectively. A persistent cross-shelf gradient in NPP is present with higher productivity rates offshore, contrasting with patterns observed along the West Antarctic Peninsula. Embayment productivity is intimately tied to sea ice dynamics, with large interannual variability in NPP rates driven by open water area and the timing of embayment opening. Opening of the embayment is linked to periods of positive Southern Annular Mode and stronger westerlies, which lead to the vertical deflection of warm, maritime air over the peninsula and down the leeward side causing increases in surface air temperature and wind velocity. High productivity in these new polynyas is likely to have ramifications for organic matter export and marine ecosystem evolution.
Keywords: Sørishavet; brehylle; fjernmåling; fytoplankton; havis; isbrem; isshelf; klimaendringer; oseanografi; polynja; satellite bilder; sjøis

Antarktis: inlandsis, shelf-is och stigande havsnivå - Darelius, Elin (Naturen, 2014)
I klimatsammanhang har strålkastarljuset länge varit riktade mot de känsliga polarområdena och smältande is. Bilder på isbjörnar som klamrar sig fast vid ett ensamt isflak figurerar varje höst i media när årets – ofta rekordlåga – minimum i utbredning av Arktisk havsis offentliggörs. Men nyligen har is-överskrifterna allt oftare kommit söderifrån, de har handlat om Antarktis, om shelf-is som smälter, om en stigande havsnivå och om möjligheten för att inlandsisen i Väst-Antarktis ska kollapsa.
Keywords: Sørishavet; brehylle; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R; Nicholls, Keith W (Journal of Geophysical Research: Oceans, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; hydrografi; isfront; isshelf

On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Estimating surface mass balance variability in Antarctica: examples from Fimbulisen - Isaksson, Elisabeth (Fram forum, 2014)
If all the ice in the Antarctic ice sheet were to melt, the world’s oceans would rise about 58 metres. Although nobody expects anything that dramatic to happen, current knowledge doesn’t tell us what we might actually expect. The Fimbulisen project should help eliminate some of the uncertainty.
Keywords: Dronning Maud Land; glasiologi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Low melt rates with seasonal variability at the base of Fimbul Ice Shelf, East Antarctica, revealed by in situ interferometric radar measurements - Langley, Kirsty; Kohler, Jack; Sinisalo, Anna; Øyan, Mats Jørgen; Hamran, Svein Erik; Hattermann, Tore; Matsuoka, Kenichi; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Basal melt is a major cause of ice shelf thinning affecting the stability of the ice shelf and reducing its buttressing effect on the inland ice. The Fimbul ice shelf (FIS) in Dronning Maud Land (DML), East Antarctica, is fed by the fast-flowing Jutulstraumen glacier, responsible for 10% of ice discharge from the DML sector of the ice sheet. Current estimates of the basal melt rates of the FIS come from regional ocean models, autosub measurements, and satellite observations, which vary considerably. This discrepancy hampers evaluation of the stability of the Jutulstraumen catchment. Here, we present estimates of basal melt rates of the FIS using ground-based interferometric radar. We find a low average basal melt rate on the order of 1 m/yr, with the highest rates located at the ice shelf front, which extends beyond the continental shelf break. Furthermore, our results provide evidence for a significant seasonal variability.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbre; isshelf; kontinentalsokkel; smelting

Complex network of channels beneath an Antarctic ice shelf - Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Sinisalo, Anna; Matsuoka, Kenichi; Hattermann, Tore; Humbert, Angelika; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Ice shelves play an important role in stabilizing the interior grounded ice of the large ice sheets. The thinning of major ice shelves observed in recent years, possibly in connection to warmer ocean waters coming into contact with the ice-shelf base, has focused attention on the ice-ocean interface. Here we reveal a complex network of sub ice-shelf channels under the Fimbul Ice Shelf, Antarctica, mapped using ground-penetrating radar over a 100 km2 grid. The channels are 300–500 m wide and 50 m high, among the narrowest of any reported. Observing narrow channels beneath an ice shelf that is mainly surrounded by cold ocean waters, with temperatures close to the surface freezing point, shows that channelized basal melting is not restricted to rapidly melting ice shelves, indicating that spatial melt patterns around Antarctica are likely to vary on scales that are not yet incorporated in ice-ocean models.
Keywords: Antarktis; glasiologi; innlandsis; isshelf; satellite bilder; satellite mikrobølgesensorer

High variability of climate and surface mass balance induced by Antarctic ice rises - Lenaerts, Jan T M; Joel, Brown.; Van Den Broeke, Michiel R; Matsuoka, Kenichi; Drews, Reinhard; Callens, Denis; Philippe, Morgane; Gorodetskaya, Irina V; Van Meijgaard, Erik; Reijmer, Carleen H; Pattyn, Frank; Van Lipzig, Nicole P M (Journal of Glaciology, 2014)
Ice rises play key roles in buttressing the neighbouring ice shelves and potentially provide palaeoclimate proxies from ice cores drilled near their divides. Little is known, however, about their influence on local climate and surface mass balance (SMB). Here we combine 12 years (2001–12) of regional atmospheric climate model (RACMO2) output at high horizontal resolution (5.5 km) with recent observations from weather stations, ground-penetrating radar and firn cores in coastal Dronning Maud Land, East Antarctica, to describe climate and SMB variations around ice rises. We demonstrate strong spatial variability of climate and SMB in the vicinity of ice rises, in contrast to flat ice shelves, where they are relatively homogeneous. Despite their higher elevation, ice rises are characterized by higher winter temperatures compared with the flat ice shelf. Ice rises strongly influence SMB patterns, mainly through orographic uplift of moist air on the upwind slopes. Besides precipitation, drifting snow contributes significantly to the ice-rise SMB. The findings reported here may aid in selecting a representative location for ice coring on ice rises, and allow better constraint of local ice-rise as well as regional ice-shelf mass balance.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Basal mass budget of Ross and Filchner-Ronne ice shelves, Antarctica, derived from Lagrangian analysis of ICESat altimetry - Moholdt, Geir; Padman, Laurie; Fricker, Helen Amanda (Journal of Geophysical Research: Earth Surface, 2014)
Traditional methods of deriving temporal variability of Antarctic ice-shelf elevation from satellite altimetry use a fixed (“Eulerian”) reference frame, where the measured changes include advection of ice thickness gradients between measurement epochs. We present a new method which removes advection effects by using an independent velocity field to compare elevations in a moving (“Lagrangian”) reference frame. Applying the technique to ICESat laser altimetry for the period 2003–2009 over the two largest Antarctic ice shelves, Ross and Filchner-Ronne, we show that the Lagrangian approach reduces the variability of derived elevation changes by about 50% compared to the Eulerian approach and reveals clearer spatial patterns of elevation change. The method simplifies the process of estimating basal mass budget from the residual of all other processes that contribute to ice-shelf elevation changes. We use field data and ICESat measurements over ice rises and the grounded ice sheet to account for surface accumulation and changes in firn air content, and remove the effect of ice-flow divergence using surface velocity and ice thickness data. The results show highest basal melt rates (>5 m a−1) near the deep grounding lines of major ice streams, but smaller melt rates (<5 m a−1) near the ice-shelf fronts are equally important to total meltwater production since they occur over larger areas. Integrating over the entire ice-shelf areas, we obtain basal mass budgets of −50 ± 64 Gt a−1 for Ross and −124 ± 66 Gt a−1 for Filchner-Ronne, with changes in firn air content as the largest error source.
Keywords: Sørishavet; batymetri; brehylle; geofysikk; innlandsis; isbrem; isshelf; oseanografi; satellite altimetri

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Wind-driven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea - Zhou, Qiming; Hattermann, Tore; Nøst, Ole Anders; Biuw, Martin; Kovacs, Kit M; Lydersen, Christian (Journal of Geophysical Research: Oceans, 2014)
Abstract Solar heated, fresh Antarctic Surface Water (ASW) is a permanent feature along the Eastern Weddell Sea (EWS) coast in summer down to a depth of roughly 200 m. Recently, ASW has been observed beneath the Fimbul Ice Shelf, suggesting that it might play an important role in basal melting. We propose that wind-driven coastal downwelling is the main mechanism that spreads ASW beneath the ice shelf in this sector of Antarctica. We validate this hypothesis with observations, scaling analyses, and numerical modeling, along three principle lines: (i) data analyses of about 1500 salinity profiles collected by instrumented seals indicate that the observed freshening of the coastal water column is likely explained by the on-shore Ekman transport and subsequent downwelling of ASW; (ii) an analytical model of the coastal momentum balance indicates that wind-driven downwelling is capable of depressing the buoyant surface water to a depth similar to the ice shelf draft; and (iii) simulations from both idealized and regional eddy-resolving numerical ice shelf/ocean models support our proposition. Our main conclusion is that wind-driven spreading of ASW beneath the ice shelf occurs when downwelling exceeds the depth of the ice shelf base. Furthermore, our study adds to the understanding of the oceanic processes at the Antarctic Slope Front in the EWS, with possible implications for other sectors of Antarctica.
Keywords: Sørishavet; Weddellhavet; isbrem; isshelf; oseanografi; overflatevann; smelting; vannmasser; vannvirvler

Eddy-Driven Exchange between the Open Ocean and a Sub–Ice Shelf Cavity - Årthun, Marius; Holland, Paul R; Nicholls, Keith William; Feltham, Daniel L (Journal of Physical Oceanography, 2013)
Keywords: Sørishavet; Weddellhavet; isshelf; oseanografi; sjøvirvler; vannvirvler

Tre kilder til smelting av Fimbulisen - Hattermann, Tore; Nøst, Ole A; Smedsrud, Lars H (Klima: norsk magasin for klimaforskning, 2013)
Soloppvarmet overflatevann er en sentral varmekilde som bidrar til smelting av isbremmen Fimbulisen i Dronning Maud Land.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Seasonal inflow of warm water onto the southern Weddell Sea continental shelf, Antarctica - Årthun, Marius; Nicholls, Keith William; Makinson, Keith; Fedak, Michael A; Boehme, Lars (Geophysical Research Letters, 2012)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi

Southern Weddell Sea shelf edge geomorphology: Implications for gully formation by the overflow of high-salinity water - Gales, Jennifer A; Larter, Robert David; Mitchell, Neil; Hillenbrand, Claus-Dieter; Østerhus, Svein; Shoosmith, Deb R (Journal of Geophysical Research: Earth Surface, 2012)
Keywords: Sørishavet; Weddellhavet; forskning; geomorfologi; isshelf; oseanografi

Ice Shelf - Ocean Interaction in the Eastern Weddell Sea, Antarctica - Hattermann, Tore (Universitetet i Tromsø, 2012)
This thesis investigates the interaction of the Antarctic ice shelves along the coast of Dronning Maud Land with the ocean circulation in the Eastern Weddell Sea. A set of direct oceanic observations below the Fimbul Ice Shelf, which were acquired during three Antarctic field seasons in the austral summers 2009/10, 2010/11 and 2011/12, is a central element of the presented work. This new oceanographic dataset is complemented by a high-resolution state-of-the-art ice shelf - ocean circulation model. The results provide an estimate of the amount of basal melting at the Fimbul Ice Shelf, and revise the physical processes that determine the ocean heat fluxes over the East Antarctic continental slope. A major finding is that deep-ocean heat fluxes towards the ice are much more constrained than predicted by previous ocean models, causing substantially lower rates of basal melting than earlier suggested. The predicted basal melting is consistent with mass balance estimates from satellite data and implicates that the Fimbul Ice Shelf is currently not subject to rapid basal mass loss. Furthermore, the complex interplay of the processes within the coastal, frontal system, and their respective role in transporting heat for melting towards the ice is examined. The results emphasize the importance of oceanic eddies within the coastal circulation for controlling the inflow of Warm Deep Water into the ice shelf cavities. A realistic representation of the effect of the mesoscale eddy overturning is thus a crucial requirement in order to simulate basal melting along the Weddell Sea coast in the present and future climate. The results also imply that fresh, and solar-heated Antarctic Surface Water plays a central role for the ice shelf cavity exchange. Being produced by sea ice melting at the ocean surface, this water mass directly enters the cavity and increases the melting of shallow ice. Due to its buoyancy, the presence of Antarctic Surface Water also alters the coastal dynamics and regulates the inflow of warm water at depth, thus showing that a more detailed understanding of the role of this water mass for basal melting around Antarctica will need further attention. Finally, the results suggest a direct relationship between the simulated basal melting and only a few deterministic parameters of the coastal circulation, which is used to derive a simple parameterization of for basal melting at the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; fysikk; fysisk oseanografi; isbrem; isshelf; klimaendringer

Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Radar characterization of the basal interface across the grounding zone of an ice-rise promontory in East Antarctica - Matsuoka, Kenichi; Pattyn, Frank; Callens, Denis; Conway, Howard (Annals of Glaciology, 2012)
Radar power returned from the basal interface along a 42 km long profile over an ice-rise promontory and the adjacent Roi Baudouin ice shelf, Dronning Maud Land, East Antarctica, is analyzed to infer spatial variations in basal reflectivity and hence the basal environment. Extracting basal reflectivity from basal returned power requires an englacial attenuation model. We estimate attenuation in two ways: (1) using a temperature-dependent model with input from thermomechanical ice-flow models; and (2) using a radar method that linearly approximates the geometrically corrected returned power with ice thickness. The two methods give different results. We argue that attenuation calculated using a modeled temperature profile is more robust than the widely used radar method, especially in locations where depth-averaged attenuation varies spatially or where the patterns of basal reflectivity correlate with the patterns of the ice thickness.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Virvler øker smeltingen - Smedsrud, Lars H; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Kovacs, Kit M; Nøst, Ole A (Klima: norsk magasin for klimaforskning, 2012)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima; oseanografi

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi

Deglacial history of the West Antarctic Ice Sheet in the western Amundsen Sea Embayment - Smith, James A.; Hillenbrand, Claus-Dieter; Kuhn, Gerhard; Larter, Robert D.; Graham, Alastair G.C.; Ehrmann, Werner; Moreton, Steven G.; Forwick, Matthias (Quaternary Science Reviews, 2011)
The Amundsen Sea Embayment (ASE) drains approximately 35% of the West Antarctic Ice Sheet (WAIS) and is one of the most rapidly changing parts of the cryosphere. In order to predict future ice sheet behaviour, modellers require long-term records of ice-sheet melting to constrain and build confidence in their simulations. Here, we present detailed marine geological and radiocarbon data along three palaeo-ice stream tributary troughs in the western ASE to establish vital information on the timing of deglaciation of the WAIS since the Last Glacial Maximum (LGM). We have undertaken multi-proxy analyses of the cores (core description, shear strength, x-radiographs, magnetic susceptibility, wet bulk density, total organic carbon/nitrogen, carbonate content and clay mineral analyses) in order to: (1) characterise the sedimentological facies and depositional environments; and (2) identify the horizon(s) in each core that would yield the most reliable age for deglaciation. In accordance with previous studies we identify three key facies, which offer the most reliable stratigraphies for dating deglaciation by recording the transition from a grounded ice sheet to open marine environments. These facies are: i) subglacial, ii) proximal grounding line, and iii) seasonal open marine. In addition, we incorporate ages from other facies (e.g., glaciomarine diamictons deposited at some distance from the grounding line, such as glaciogenic debris flows and iceberg-rafted diamictons and turbates) into our deglacial model. In total, we have dated 78 samples (mainly the acid insoluble organic (AIO) fraction, but also calcareous foraminifers), which include 63 downcore and 15 surface samples. Through careful sample selection prior to dating, we have established a robust deglacial chronology for this sector of the WAIS. Our data show that deglaciation of the western ASE was probably underway as early as 22,351 calibrated years before present (cal yr BP), reaching the mid-shelf by 13,837 cal yr BP and the inner shelf to within c.10–12 km of the present ice shelf front between 12,618 and 10,072 cal yr BP. The deglacial steps in the western ASE broadly coincide with the rapid rises in sea-level associated with global meltwater pulses 1a and 1b, although given the potential dating uncertainty, additional, more precise ages are required before these findings can be fully substantiated. Finally, we show that the rate of ice-sheet retreat increased across the deep (up to1600 m) basins of the inner shelf, highlighting the importance of reverse slope and pinning points in accelerated phases of deglaciation.
Keywords: Amundsenhavet; Sørishavet; deglasiasjon; glasiologi; innlandsis; isshelf; marin geologi

ICE Fimbulisen - top to bottom: season 2 expedition field report - Tronstad ed., Stein; Polarinstitutt, Norsk (Norsk Polarinstitutt, 2011)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; logistikk; oseanografi

Observations of the Antarctic Slope Undercurrent in the southeastern Weddell Sea - Chavanne, Cédric P; Heywood, Karen J; Nicholls, Keith W; Fer, Ilker (Geophysical Research Letters, 2010)
The Antarctic Slope Front presents a dynamical barrier between the cold Antarctic shelf waters in contact with ice shelves and the warmer subsurface waters offshore. Two hydrographic sections with full-depth current measurements were undertaken in January and February 2009 across the slope and shelf in the southeastern Weddell Sea. Southwestward surface-intensified currents of ∼30 cm s−1, and northeastward undercurrents of 6–9 cm s−1, were in thermal-wind balance with the sloping isopycnals across the front, which migrated offshore by 30 km in the time interval between the two sections. A mid-depth undercurrent on February 23 was associated with a 130-m uplift of the main pycnocline, bringing Warm Deep Water closer to the shelf break. This vertical displacement, comparable to that caused by seasonal variations in wind speed, implies that undercurrents may affect the exchanges between coastal and deep waters near the Antarctic continental margins.
Keywords: Sørishavet; Weddellhavet; hydrografi; isbrem; isshelf; kontinentalmargin; kontinentalsokkel; oseanografi; understrømmer

Land and sea-ice properties in Antarctica: bridging the gap between the ground and satellite measurements in the western Ross Sea region - Rack, Wolfgang; Langhorne, Pat; Haas, Christian; Clavano, Wendy; Gough, Alex; Kruetzmann, Nikolai; Pinchin, James; Riger-Kusk, Mette (Ice and climate news, 2010)
Keywords: Antarktis; Sørishavet; glasiologi; havis; isshelf

Biogeochemical weathering under ice: Size matters - Wadham, Jemma L; Tranter, Martyn; Skidmore, Mark; Hodson, Andy; Priscu, John C; Lyons, W Berry; Sharp, Martin; Wynn, Peter; Jackson, Miriam (Global Biogeochemical Cycles, 2010)
The basal regions of continental ice sheets are gaps in our current understanding of the Earth's biosphere and biogeochemical cycles. We draw on existing and new chemical data sets for subglacial meltwaters to provide the first comprehensive assessment of sub-ice sheet biogeochemical weathering. We show that size of the ice mass is a critical control on the balance of chemical weathering processes and that microbial activity is ubiquitous in driving dissolution. Carbonate dissolution fueled by sulfide oxidation and microbial CO2 dominate beneath small valley glaciers. Prolonged meltwater residence times and greater isolation characteristic of ice sheets lead to the development of anoxia and enhanced silicate dissolution due to calcite saturation. We show that sub-ice sheet environments are highly geochemically reactive and should be considered in regional and global solute budgets. For example, calculated solute fluxes from Antarctica (72–130 t yr−1) are the same order of magnitude as those from some of the world's largest rivers and rates of chemical weathering (10–17 t km−2 yr−1) are high for the annual specific discharge (2.3–4.1 × 10−3 m). Our model of chemical weathering dynamics provides important information on subglacial biodiversity and global biogeochemical cycles and may be used to design strategies for the first sampling of Antarctic Subglacial Lakes and other sub-ice sheet environments for the next decade.
Keywords: Antarktis; biogeokjemi; biosfære; brehylle; glasiologi; innlandsis; isbrem; isshelf; subglasial biodiversitet; subglasial innsjø